HIGH-TECHNOLOGY SEED REFINER - Andrey V. Butovchenko (Advanced Engineering Research)
High technological effectiveness of the seed refiner, which permits to get seed grain in one clearing cycle and which includes an effective separation of the primary treatment and an effective separation of the seed treatment, is proved.